Dehumanization of Village Financial Management: Erich Fromm's Perspective Accounting Reconstruction - Puja Rizqy Ramadhan; Fitri Yani Panggabean; Nia Pratiwi Lubis (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to reconstruct village financial management using modernity vis a dehumanization perspective. This study uses primary data obtained from observations and interviews with informants. The research approach used is a qualitative method. The research paradigm uses the paradigm of criticism with data collection procedures, data presentation, data reduction and conclusion/verification. The results showed that the modernization and digitization of financial management in Klambir V Kebun Village had an impact on social relations in the community, which became less harmonious. For this reason, it is necessary to carry out an accounting reconstruction based on modernity vis a vis dehumanizaton perspective that is relevant to be carried out in Klambir V Kebun Village